Capital as Power in the Creative Industries: A Case Study of Freelance Creative Work in the Netherlands - Frederick Harry Pitts (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2016)
Using Nitzan and Bichler's understanding of the dissonant relationship between creativity and power and business and industry, this paper investigates the rhythms of freelance creative work. It reports findings from interviews conducted with freelancers working in the Dutch creative industries. The findings suggest that freelancers enjoy more responsibility and autonomy than formal employees. But this autonomy represents a risk that their clients must manage. Different client relationships, and the proximity they imply, produce different rhythms. The research explores freelancers' experiences of these rhythms in graphic design, advertising and branding. The research begins from the premise that risk and responsibility are both assumed and apportioned as a function of relationships of power and discipline in the sphere of work. Freelancers are agents of the management of these two interrelated categories. They are subject to the competing rhythms implied by the relation between these two categories. With reference to these rhythms, the research draws upon Nitzan and Bichler's theory of `capital as power' as an analytical tool. Nitzan and Bichler develop a conceptualisation of the tension between `industry' and `business'. This explains how the latter sabotages the creativity of the former. This produces a `dissonance' between the two. This dissonance is the productive driving force of capital accumulation. Applying this to the relationship of risk and responsibility in freelance creative work, I explore how these differing rhythms manifest. The conflict between the freedom to be creative and the management of creativity is not a deficiency of creative production. Rather, it is its moving principle.
Keywords: 330; capital as power; dissonance; freelance; resonance; risk